Figurative art in Soviet Russia circa 1921-1934 : situating the realist-anti-realist debate in the context of changing definitions of proletarian culture - Nolte, Jacqueline Elizabeth (Michaelis School of Fine Art, 2016)
Bibliography: p. 247-263.